Performance of Peking Ducks (Anas plathyrinchos) Adding Kencur Flour (Kaemferia galanga) in their rations - Herlina, Betty; Suningsih, Nining; Setiyani, Setiyani (JURNAL ILMIAH PETERNAKAN TERPADU, 2021)
The research objective was to determine the performance of Peking ducks which were added with galangal flour in their rations. The research method was an experimental method using a completely randomized design with 6 treatments and 4 replications where each replication consisted of 4 ducks. The study was conducted for 56 days. The research materials were 96 Day Old Ducks, rations (milled corn, bran, tofu dregs, and kale waste), drinking water, sugar water and calx. The equipment used were a stage cage, a litter, a place for feeding and drinking, a scale, stationery and other equipment. The treatments consisted of P0 = basal ration, P1 = P0 + 0.1% galangal flour, P2 = P0 + 0.2% galangal flour, P3 = P0 + 0.3% galangal flour, P4 = P0 + 0.4% galangal flour, and P5 = P0 + 0.5% galangal flour. The variables observed were feed consumption, body weight gain, feed conversion, and mortality. Data were analysed using analysis of variance. The results showed that the addition of galangal flour in the ration had a significant effect (P <0.05) on ration consumption and body weight gain and had no significant effect (P> 0.05) on ration conversion and mortality. The conclusion of this research is that the performance of Peking ducks which were given the addition of galangal flour in the ration could increase the feed consumption and body weight gain, but has not been efficient in reducing the value of feed conversion and the percentage of mortality.